Penetapan Kadar Vitamin C Pada Cabai Rawit (Capsicum Frutescens L.) Secara Iodimetri - Ainun Naim; Ranensy Chika Lacherin (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2021)
Research on Determination of Vitamin C Levels in Cayenne Pepper (Capsicum frutescens L.) has been carried out by iodimetry. The results of this study were carried out using the Iodimetric Titration method, the levels of vitamin C in cayenne pepper were 0.07498% w/b.